Narcolepsy - Margolis, Jason; Fanlight Productions (Boston, MA : Fanlight Productions, 2000)
Presents the experiences of three individuals whose lives and relationships have been disrupted by narcolepsy. Intertwined with their stories it offers solid, comprehensive scientific information about this disorder
Produced at University of California at Berkeley Graduate School of Journalism
Narrator; Alex Cohen
DVD format
Keywords: Narcolepsy; Sleep disorders